Sequestration of synaptic proteins by alpha-synuclein aggregates leading to neurotoxicity is inhibited by small peptide - Choi, Mal-Gi (PLoS One, 2018)
α-Synuclein (α-syn) is a major component of Lewy bodies found in synucleinopathies including Parkinson’s disease (PD) and Dementia with Lewy Bodies (DLB). Under the pathological conditions, α-syn tends to generate a diverse form of aggregates showing toxicity to neuronal cells and able to transmit across cells. However, mechanisms by which α-syn aggregates affect cytotoxicity in neurons have not been fully elucidated. Here we report that α-syn aggregates preferentially sequester specific synaptic proteins such as vesicle-associated membrane protein 2 (VAMP2) and synaptosomal-associated protein 25 (SNAP25) through direct binding which is resistant to SDS. The sequestration effect of α-syn aggregates was shown in a cell-free system, cultured primary neurons, and PD mouse model. Furthermore, we identified a specific blocking peptide derived from VAMP2 which partially inhibited the sequestration by α-syn aggregates and contributed to reduced neurotoxicity. These results provide a mechanism of neurotoxicity mediated by α-syn aggregates and suggest that the blocking peptide interfering with the pathological role of α-syn aggregates could be useful for designing a potential therapeutic drug for the treatment of PD.